Habituation of Short Surah Memorization to Develop Discipline in Early Childhood: A Faith-Based Character Education Approach - Tiwuk; Lestari, Gunarti Dwi; Yulianingsih, Wiwin; Zakariyah, M Fahmi (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2025)
Amid growing concerns regarding the erosion of self-regulation and rule adherence among young learners, this study investigates how short surah memorization contributes to discipline formation in early childhood. Conducted at TK Islam Bakti IV Surabaya, this qualitative case study involved students, teachers, and parents participating in a structured Quranic memorization program. Data were collected through observations, in-depth interviews, and document analysis, then processed using Miles and Huberman’s interactive model. The findings demonstrate that daily memorization routines significantly enhance children’s discipline, particularly in the areas of punctuality, responsibility, rule-following, and focus. Students who engaged consistently in memorization exhibited observable improvements in time management, task commitment, and behavioral self-regulation. Teachers structured learning schedules around specific surah targets, while parents extended reinforcement at home, creating a cohesive framework of habituation. Furthermore, spiritual motivation among students emerged as a strong internal driver sustaining disciplined behavior beyond external supervision. These outcomes affirm that religious memorization is not merely cognitive training but also a means of cultivating character values. The study highlights the significance of integrating faith-based habituation into early childhood character education to promote behavioral consistency and moral grounding. Nonetheless, the findings are limited by the single-site nature of the study and its culturally homogeneous participants. Broader research across diverse settings is recommended to validate the effectiveness of Quranic memorization in discipline development. Educational institutions are encouraged to design character education programs that harmonize religious values with structured behavioral reinforcement to support holistic child development.